Recycling of Mine Wastes as Ceramic Raw Materials: An Alternative to Avoid Environmental Contamination - Menezes, Romualdo Rodrigues; Santana, Lisiane Navarro L.; Neves, Gelmires Araújo; Ferreira, Heber Carlos (IntechOpen, 2012)
None